Use of Leaves as Bio-Indicator to Assess Air Pollution Tolerance Index (APTI) And Elemental Concentration of Heavy Metals at Katsina Central Market Grinding Area, Katsina State-Nigeria (International Journal of Scientific Research in Science and Technology, 2024)
Monitoring air pollution and environmental health are essential to ensure viable cities. Air pollution Tolerance Index (APTI) is used to assess how tolerant plant species are of air pollution, it can also serve to identify tolerant plant species that can be useful for pollution removal. APTI is calculated from parameters that are affected by air pollutants, such as ascorbic acid content, total chlorophyll content, relative water content, and PH of leaf extract. In this study, we compared APTI values of Ficus citrifolia leaves between control and grinding areas. The results revealed that APTI value of F. citrifolia leaves in the control area is high compared to that from the grinding site. Heavy metal concentrations were also studied. Correlation between APTI values and elemental concentrations indicated that F. citrifolia leaves were sensitive to air pollution. Thus, the APTI of tree leaves is useful proxy measure of air pollution.